Experimental investigation of modified bentonite clay-crumb rubber concrete. (10th February 2020) - Adeboje, Adeyemi Oluwaseun; Kupolati, Williams Kehinde; Sadiku, Emmanuel Rotimi; Ndambuki, Julius Musyoka; Kambole, Chewe
Highlights: Microstructure and composition of concrete materials were investigated. Fine aggregates (sand and crumb rubber) and coarse aggregate (stone) were characterized. Suitability of bentonite clay as a partial substitute of cement in concrete was evaluated. Suitability of crumb rubber as a partial replacement of sand was evaluated. Joint replacement of cement and sand with bentonite clay and crumb rubber. Abstract: This study was carried out to investigate the effects of jointly replacing cement and sand with bentonite clay and crumb rubber on the engineering properties of 25 MPa concrete. The materials used for the study were cement, bentonite clay, sand, crumb rubber, stone and water. Microstructural formation, elemental compositions and crystalline phases of cement, bentonite clay, sand, crumb rubber and stone were determined by using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDS) and X-ray Diffraction (XRD) experiments respectively. Geotechnical properties of fine aggregates (sand and crumb rubber) and coarse aggregate (stone) were determined from sieve analysis, fineness modulus, moisture content, apparent relative density and bulk density experiments. Water samples were evaluated with pH and conductivity tests. Mechanical properties of the modified bentonite clay-crumb rubber concrete were evaluated with slump, bulk density, compressive strength and tensile splitting strength tests. The microstructural formation and elemental composition of the concrete were also evaluated with the aid of SEM and EDS respectively. The results revealed that the constituent materials possessed adequate engineering requirements for the production of concrete. The modified bentonite clay-crumb rubber concrete showed comparable mechanical and microstructural properties to that of plain concrete and can be suitable for the construction of driveways, floors and walkways.